Effect of NPK Fertilizer Dosage and Number of Seeds On The Growth and Production of Two Cob Rice (Oryza Sativa L.) Variety of Rajasa 01 - Zeni Abdi; Sudarma Sudarma; Rolita Rolita (Syntax Literate, 2022)
“Effect of NPK Fertilizer Dosage and Number of Seeds on Growth and Yield of Two Cob Rice (Oryza sativa L.) Rajasa 01 varieties". This study aimed to determine the effect of NPK fertilizer and the number of seeds on the growth and yield of two cob rice varieties, Rajasa 01. This research was carried out in Lubang Indah Village, Lawe Alas District, Southeast Aceh Regency, from January to April 2021. The materials used in this study were 5 kg Rajasa 01 rice seeds (cob rice), the essential fertilizer used in this research. Used solid compost and NPK fertilizer. The design used in this study was a Randomized Block Design (RAK) with two factorial studies. The first factor is the effect of the dose of NPK fertilizer (N), which consists of 3 levels, N1: 200 kg/ha, N2: 250 kg/ha, and N3: 300 kg/ha. The second factor is the number of seeds per planting hole (J), which consists of 3 levels, J1: 1 seed/planting hole, J2: 2 seeds/planting hole, and J3: 3 seeds/planting hole. There were nine treatment combinations and three replications, so there were 27 experimental plots. Observations of growth components were observed starting from the emergence of shoots to yield, namely plant height (cm), number of tillers of rice plants per Clump, number of grains per panicle, panicle length per Clump (cm), and weight per 1000 grains of grain. The results showed that the dose of NPK fertilizer significantly affected the variables of plant height at 60 DAP and 1000 grain weight. However, it had no significant effect on the variables of plant height at 30 and 45 DAP, number of tillers per Clump at 30, 45, and 60 DAP, number of panicles per Clump, panicle length per Clump, number of grain per panicle, plant height at 60 DAP and 1000 grain weight. The highest grain was found at 300 kg/ha (N3) dose of NPK fertilizer. The number of rice seeds significantly affects the weight of 1000 grains and the number of grains per panicle. However, it had no significant impact on the variables of plant height and several tillers per Clump at the age of 30, 45, and 60 DAP; the number of panicles per Clump, panicle length per Clump, and the highest plants were found in 2 seedlings/planting hole (J2). There was no significant interaction between the treatment dose of NPK fertilizer and the number of rice seedlings on all observed variables.